2018
DOI: 10.30560/jems.v1n3p54
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Telecommuting on Employees’ Performance

Abstract: This work examined the impact of telecommuting on employees’ performance. The dynamic nature of the environment in which our organizations operate and customers need made this investigation very necessary. The objectives of the study were; to find out if arrangement that enables employee to work at home has a positive relationship with better quality of work and to ascertain whether an arrangement that allows employee to work at agreed location has significant relationship with speedy service delivery. To achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Different elements of job autonomy can be traced in organizations including (but not limited to): work method, work schedule, pace of work, work procedures, workplace, work evaluation, working hours, kind of work and amount of work, goals, priorities and work criteria (De Jonge, 1995). Telecommuting (Onyemaechi et al , 2018), flexible working hours (Kattenbach, Demerouti & Nachreiner, 2010;Beckmann, 2016), and job sharing (Ivancevich & Konopaske, 2013) are among sub-divisional areas of job autonomy that are practiced in numerous organizations. Job autonomy is considered within the process of job design in human resource management.…”
Section: Introductionmentioning
confidence: 99%
“…Different elements of job autonomy can be traced in organizations including (but not limited to): work method, work schedule, pace of work, work procedures, workplace, work evaluation, working hours, kind of work and amount of work, goals, priorities and work criteria (De Jonge, 1995). Telecommuting (Onyemaechi et al , 2018), flexible working hours (Kattenbach, Demerouti & Nachreiner, 2010;Beckmann, 2016), and job sharing (Ivancevich & Konopaske, 2013) are among sub-divisional areas of job autonomy that are practiced in numerous organizations. Job autonomy is considered within the process of job design in human resource management.…”
Section: Introductionmentioning
confidence: 99%
“…Telecommuting offers employee with several benefits that will enhance their working and personal life. Onyemaechi et al (2018) posit that telecommuting allows more flexibility in employee's schedule which helps them to respond quickly in case of unexpected events. Furthermore, (Fazrida et al, 2018) stated that telecommuting offers opportunity for working parents to balance their work and personal needs.…”
Section: Telecommutingmentioning
confidence: 99%
“…[7] Onyemaechi et al (2018) conducted a survey of telecommute (remote) workers to identify the impact of remote work on performance. The parameters that were used to assess performance were better quality of work and speedy delivery of service.…”
Section: Impact Of Remote Work On Labor Productivitymentioning
confidence: 99%
“…However, increased monitoring and supervision should be implemented to enhance the quality of work. [8] The paper by Onyemaechi et al (2018) demonstrated a positive response to telecommute work among employees. However, the survey was found to be highly subjective in nature and did not collect responses from supervisors or management who are better qualified to rate the quality of work.…”
Section: Impact Of Telecommuting On Employees' Performancementioning
confidence: 99%